Degraded products generated by iron stent inhibit the vascular smooth muscle cell proliferation by downregulating AP-1 - Jiabing Huang; Bingjian Liu; Chunguang Zhao; Jing Li; Dongxu Qiu (Journal of Materials Science: Materials in Medicine)
Abstract In-stent restenosis (ISR) following interventional therapy is a fatal clinical complication. Current evidence indicates that neointimal hyperplasia driven by uncontrolled proliferation of vascular smooth muscle cells (VSMC) is a major cause of restenosis. This implies that inhibiting VSMC proliferation may be an attractive approach for preventing in-stent restenosis. In our previous study, we found that the iron stent reduced the neointimal hyperplasia in an atherosclerotic artery stenosis model, and the iron corroded granules generated by the iron stent inhibited neointimal hyperplasia by suppressing the proliferation of VSMCs. However, this observation needs to be validated through in vitro experimentation. In this study, co-culture experiments and flow cytometer assays were performed to qualitatively investigate the effects of iron stent degradation on VSMCs. Moreover, the degraded products resulting generated by the iron stent were collected and used to elucidate the suppressive effect of the iron stents. The underlying mechanism was explored through molecular biology assays. The major findings are as follows: 1) The degraded iron stent inhibited the proliferation of VSMCs; 2) The degraded products of the iron stent downregulated the expression of AP-1. In summary, this study demonstrates the inhibitory effect of degraded iron products on VSMC proliferation, implying that such products have the potential to mitigate in-stent restenosis. Graphical Abstract degraded products generated from iron stent inhibit the vascular smooth muscle cell proliferation by downregulating AP-1.